2000
DOI: 10.1161/01.cir.101.11.1324
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Defibrillation With Triphasic Waveforms

Abstract: Background —It has been reported that triphasic defibrillation waveforms cause less myocardial injury than biphasic waveforms. This study compared the defibrillation thresholds (DFTs) of triphasic and biphasic waveforms. Methods and Results —DFTs were determined for a transvenous lead system and a 300-μF-capacitor defibrillator. In 8 pigs (group 1), DFTs were determined for 5 triphasic waveforms with tilts of 80%, 83%, and 86% and for 1 biphasic wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
(32 reference statements)
0
6
0
3
Order By: Relevance
“…Quadriphasics show superior performance but only when the patient’s impedance is elevated [13]. Polarity may also affect the relative efficacy of triphasic waveforms [14]. Thus, triphasics may indeed be superior in some models or under certain conditions but based on our findings and the body of evidence, we conclude that triphasic waveforms cannot be considered uniformly superior to biphasic waveforms.…”
Section: Discussionmentioning
confidence: 74%
“…Quadriphasics show superior performance but only when the patient’s impedance is elevated [13]. Polarity may also affect the relative efficacy of triphasic waveforms [14]. Thus, triphasics may indeed be superior in some models or under certain conditions but based on our findings and the body of evidence, we conclude that triphasic waveforms cannot be considered uniformly superior to biphasic waveforms.…”
Section: Discussionmentioning
confidence: 74%
“…Com base em consultoria estatística, os animais foram subdivididos em quatro grupos segundo: Grupo I: quatro animais, empregado o protótipo de equipamento a 50 J (PO-DEA 50 J); Grupo II: quatro animais, empregado o protótipo de equipamento a 100 J (PO-DEA 100 J); Grupo III: quatro animais, empregado o equipamento referência a 50 J (R-DEA 50J); e Grupo IV: quatro animais, empregado o equipamento referência a 100 J (R-DEA 100 J) (Quadro 1). A avaliação estatística para definição do número de animais para o estudo foi baseada em estudos publicados que envolvem o sistema cardiovascular, como o experimento de Walker et al, 14 que avaliou a eficácia de seis formas de onda em episódio de fibrilação ventricular comparando choques monofásicos de 200 J e bifásicos de 150 J em grupos de seis e oito suínos, o de Li et al, 16 onde foi estudada a eficácia das formas de ondas bifásicas pulsada e retilínea utilizando seis porcos domésticos, e o de Huang et al, 20 que comparou os limiares de desfibrilação das formas de onda trifásica e bifásica em grupos de oito porcos. A ordem dos animais para a realização dos experimentos foi randomizada para os grupos e de forma cega para os laboratórios de análise.…”
Section: Artigo Original / Original Articleunclassified
“…All of these factors have been implicated as determinants of defibrillation efficacy. Although triphasic waveforms have been shown to be superior to biphasic ones in some circumstances (40,42), other studies have shown no difference or even a trend to superiority of the biphasic shape (13,25,44,57). After clinical trials (9), the biphasic waveform has become the clinical standard for implantable devices.…”
Section: Waveformsmentioning
confidence: 99%